Comprehensive Review of HaridraÌ„ and DaÌ„ruharidraÌ„di KasÌaÌ„ya on Diabetic Retinopathy - Gajabhe, Pragati R. (International Journal of Pharmaceutical & Biological Archive, 2017)
Ayurveda is being seen as a source of leads for discovery of novel molecules. The management of diabetes has been elaborately discussed in Ayurvedic texts. There are number of herbs and herbal preparations that are being used in Ayurveda for the management of diabetes for centuries. Some of these herbs and herbal preparations are also indicated as a treatment of timira. We, therefore, considered these herbal preparations as the starting point to carry out our preliminary investigation to get leads for the management of diabetic retinopathy.